1961
DOI: 10.1152/jappl.1961.16.3.522
|View full text |Cite
|
Sign up to set email alerts
|

Single-breath analysis of carbon dioxide concentration records

Abstract: A fourth-degree equation has been employed to describe the capnogram. By means of its derivative functions two flexion points can be determined, VeI and VeII, the former corresponding to the maximal increase in |FeCO2|, the latter to the minimal increase, i.e., to the beginning of the alveolar phase. The dead space exhaled can be expressed as a continuous function by an equation using the integral function of the empirical curve. The experimental curve (capnogram) has been divided into four phases: lag, where … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Early studies, in the 1960s, focused on characterizing the shape of the capnogram in normal subjects (3), on demonstrating differences between their capnograms and capnograms from OD subjects (4,8,9), and on determining the physiological mechanisms underlying the capnogram changes in OD (3,(5)(6)(7). More recent studies, in the mid-1990s, demonstrated a correlation between FEV 1 and the shape of the capnogram in adult asthma subjects (10,11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early studies, in the 1960s, focused on characterizing the shape of the capnogram in normal subjects (3), on demonstrating differences between their capnograms and capnograms from OD subjects (4,8,9), and on determining the physiological mechanisms underlying the capnogram changes in OD (3,(5)(6)(7). More recent studies, in the mid-1990s, demonstrated a correlation between FEV 1 and the shape of the capnogram in adult asthma subjects (10,11).…”
Section: Discussionmentioning
confidence: 99%
“…The capnogram achieves a maximal value at the end of exhalation (the end-tidal CO 2 [ETco 2 ] concentration) then decreases rapidly to zero as inhalation begins ( Fig. 1) (1)(2)(3)(4).…”
mentioning
confidence: 99%
“…The normal capnogram has an almost square wave pattern (Fig. 1 ), marked by alternating inspiratory (P insp CO 2 equals zero) and expiratory phases [ 3 , 4 ]. Expiration itself consists of three successive phases: (1) a latency phase (phase 1), corresponding to the expiration of the anatomical dead space (P exp CO 2 equals zero), which is indistinguishable from the preceding inspiration; (2) slope phase (phase 2) marked by a very rapid rise in P exp CO 2 , corresponding to expiration of mixed air; and (3) plateau phase (phase 3), reflecting the elimination of alveolar air (slightly increasing P exp CO 2 ) resulting in a peak at the end of tidal expiration (P et CO 2 close to alveolar carbon dioxide tensions P A CO 2 ) [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The normal capnogram ( fig. 1a) has a square wave pattern, marked by alternating inspiratory (PICO 2 equals zero) and expiratory phases [1][2][3]. Expiration itself consists of three successive phases: 1) a latency phase, "E1", corresponding to expiration of the anatomical dead space (PECO 2 =0), indistinguishable from the preceding inspiration; 2) phase "E2", marked by a very rapid rise in PECO 2 , corresponding to expiration of mixed air; and 3) plateau phase, "E3", reflecting the elimination of alveolar air (slightly increasing PECO 2 ) resulting in a peak at the end of tidal expiration (PETCO 2 , close to alveolar carbon dioxide tension (PAco 2 )), which immediately precedes the start of the following inspiration.…”
mentioning
confidence: 99%